2008
DOI: 10.3189/002214308786570782
|View full text |Cite
|
Sign up to set email alerts
|

Planimetric and volumetric glacier changes in the Khumbu Himal, Nepal, since 1962 using Corona, Landsat TM and ASTER data

Abstract: Multitemporal space imagery from 1962 (Corona KH-4), 1992 (Landsat TM), 2001 and 2005 (Terra ASTER) was used to investigate the glacier changes in the Khumbu Himal, Nepal. The ice coverage in the investigation area decreased by about 5% between 1962 and 2005, with the highest retreat rates occurring between 1992 and 2001. The debris coverage increased concomitantly with the decrease in total glacier area. The clean-ice area decreased by >10%. Digital terrain model (DTM) generation from the early Corona KH-4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
271
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(305 citation statements)
references
References 27 publications
25
271
0
1
Order By: Relevance
“…And although melting is expected to be reduced under the debris cover on these lower glacier parts (e.g. Benn & Lehmkuhl, 2000), the surface properties possibly have only limited influence on the melting: In their study in the Himachal Pradesh, Berthier et al (2007) observed the strongest lowering of glacier surfaces at low elevations, independent of the amount of debris cover; Gardelle et al (2012) made similar findings in the Karakoram, Bolch et al (2008) in the Mt. Everest region, and Paul & Haeberli (2008) in the European Alps.…”
Section: Glacier Inventory Datasupporting
confidence: 49%
See 1 more Smart Citation
“…And although melting is expected to be reduced under the debris cover on these lower glacier parts (e.g. Benn & Lehmkuhl, 2000), the surface properties possibly have only limited influence on the melting: In their study in the Himachal Pradesh, Berthier et al (2007) observed the strongest lowering of glacier surfaces at low elevations, independent of the amount of debris cover; Gardelle et al (2012) made similar findings in the Karakoram, Bolch et al (2008) in the Mt. Everest region, and Paul & Haeberli (2008) in the European Alps.…”
Section: Glacier Inventory Datasupporting
confidence: 49%
“…Bolch et al, 2008;Bhambri et al, 2011). In higher latitudes, illumination differences caused by the convex shape of the tongues or the break in slope at the contact to lateral moraines can be used to track glacier boundaries (cf.…”
Section: Mapping Of Debris-covered Glacier Partsmentioning
confidence: 99%
“…iteratively shifting one DEM to the other within a ±5 pixel window (Rodriguez et al, 2006;Berthier et al, 2007;Howat et al, 2008). Other studies have corrected DEMs using single or multiple linear regression corrections between elevation and the location and terrain parameters (Gorokhovich and Voustianiouk, 2006;Bolch et al, 2008;Peduzzi et al, 2010). In terrestrial and airborne laser scanning, 3-D Least Squares Matching (LSM) is used to minimize the Euclidean distances between the points of point clouds, often allowing not only for shifts but also for rotations and scales between the two or more datasets (Gruen and Akca, 2005;Miller et al, 2009).…”
mentioning
confidence: 99%
“…In the last decades, the availability of low-cost data from optical remote sensing platforms with global coverage provided opportunities for glacier mapping at regional scales. Remote sensing techniques have considerably helped improve estimates of glacier area changes (Bhambri et al, 2010;Bolch, 2007;Bajracharya et al, 2007;Kamp et al, 2011;Bolch et al, 2008a), glacier lake changes (Bajracharya et al, 2007;Bolch et al, 2008b;Gardelle et al, 2011;Wessels et al, 2002) and region-wide glacier mass balance Bolch et al, 2011;Gardelle et al, 2013;Kääb et al, 2012), but significant gaps do remain. The new global Randolph Glacier Inventory (RGI) v.4 (Pfeffer et al, 2014) provides a global data set of glacier outlines intended for largescale studies; however, in some regions the quality varies and the outlines may not be suitable for detailed regional analysis of glacier parameters.…”
Section: Introductionmentioning
confidence: 99%